Moderní analýza biologických dat : 2. díl. Lineární modely s korelacemi v prostředí R. - Brabec, Marek (Masarykova univerzita, 2012)
The publication follows the first volume of Modern analysis of biological data and presents selected models and methods of statistical analysis of correlated data. Linear methods are useful in analysis of data with temporal, spatial or phylogenetic correlations. The book is a practical handbook of data analysis in one of world's biggest statistical tools, freeware R. There are 19 resolved and commented examples that show correct ways of model construction and point out possible mistakes that can occur during data analysis. The text is open for all readers; special mathematical education is not.